EFFECTIVE WAYS OF LEARNING ENGLISH - Azamatova Muxlisa Ilyos qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: One of the most effective and easiest ways to learn English is to fully immerse yourself in the language. Start listening to English speeches or conversations. Watch a movie or TV show, or surround yourself with people who are conversing in English. To do this, find a radio station that speaks that language. Listen carefully to speeches and conversations and try to use the language every day. Not only will this help your listening skills, but you can also try to pronounce the words in context yourself to improve your speaking skills. With modern technology and applications, this can be done almost anywhere.